The flourishing of Islamic reformism in Iran : political Islamic groups in Iran (1941-61) - Taqavī, Muḥammad ʻAlī (RoutledgeCurzon, 2004)
During the 1940s and 1950s, Islamic reformism flourished in Iran. This book examines how Iranian Islamic groups came to rethink traditional accounts of religion and nurture a politicized version of Islam.
Keywords: Islam and politics -- Iran.; Islamic renewal -- Iran.; Renouveau islamique -- Iran.; RELIGION -- Islam -- Theology.; Islam and politics; Islamic renewal; Iran; Islam; Fundamentalismus; Politik